2017
DOI: 10.1038/s41598-017-00814-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Enrichment and Sequencing of Recent Endosymbiont-Host Lateral Gene Transfers

Abstract: Lateral gene transfer (LGT) from microbial symbionts to invertebrate animals is described at an increasing rate, particularly between Wolbachia endosymbionts and their diverse invertebrate hosts. We sought to assess the use of a capture system to cost-effectively sequence such LGT from the host genome. The sequencing depth of Illumina paired end data obtained with a Wolbachia capture system correlated well with that for an Illumina paired end data set used to detect LGT in Wolbachia-depleted B. malayi (p-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The genome sequence of the Wolbachia culture isolated from D. citri was completely assembled and compared with other Wolbachia genomes available in the NCBI database. This study is in accordance with the study by Sinha et al 25 , which demonstrated that high quality, complete Wolbachia genome assemblies can be achieved from long-read sequences of high coverage without enrichment, such as through Large Enriched Fragment Targeted Sequencing 67 and other target genome enrichment techniques 68 , 69 . In this study, we used DNA from an axenic Wolbachia cultures for whole genome sequencing rather than filtering Wolbachia sequence reads from the whole insect genome sequence.…”
Section: Discussionsupporting
confidence: 91%
“…The genome sequence of the Wolbachia culture isolated from D. citri was completely assembled and compared with other Wolbachia genomes available in the NCBI database. This study is in accordance with the study by Sinha et al 25 , which demonstrated that high quality, complete Wolbachia genome assemblies can be achieved from long-read sequences of high coverage without enrichment, such as through Large Enriched Fragment Targeted Sequencing 67 and other target genome enrichment techniques 68 , 69 . In this study, we used DNA from an axenic Wolbachia cultures for whole genome sequencing rather than filtering Wolbachia sequence reads from the whole insect genome sequence.…”
Section: Discussionsupporting
confidence: 91%
“…The LGT analysis revealed presence of three candidates (see Additional file 1 : Stomoxys lateral gene transfer, Table S7), all of which were derived from Wolbachia , a common endosymbiont found in arthropods [ 82 ] that infects 40–60% of insect species [ 83 , 84 ]. Wolbachia are a common source of LGTs [ 85 , 86 ], likely due to their association with the germline of their insect hosts. The three candidates were examined for sequencing read depth in the candidate LGT and flanking DNA to determine if there were large changes in read depth across the junction that would be indicative of miss-assembly to contaminating bacterial DNA (see Additional file 1 : Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this case a high sequencing depth per genome is needed, as typically only a small proportion of the reads will be of Wolbachia origin. For more efficient sequencing of Wolbachia genomes, target enrichment protocols (Lemmon & Lemmon 2012) have been established (Geniez et al 2012;Dunning-Hotopp et al 2017), although these are not yet broadly applied.…”
Section: Alternatives To Mlstmentioning
confidence: 99%